Reconnoitering Price Discovery and Market Efficiency Process Among Indian HRITHIK Stocks Using VAR Causality and VECM Tests - Gupta, Nupur; Dalal, Yash (Indian Journal of Finance, 2022)
The purpose of this paper was to ascertain the impact of futures prices on market efficiency and price discovery in India in HRITHIK stocks from 2017 – 2020. The paper investigated the impact of futures prices on market efficiency and price discovery in India in HRITHIK stocks from 2017 – 2020. The current study comprised the daily near-month futures and daily spot closing prices of the HRITHIK stocks from January 1, 2017 – December 31, 2020, including the COVID-19 pandemic period. The paper used the vector autoregression (VAR) Engel Granger causality test to test the short-run equilibrium between spot and futures prices and the vector error correction model (VECM) to test for long-run equilibrium. A bi-directional relationship was found among six stocks out of the seven HRITHIK stocks. This confirmed the causal relationship that futures prices have on the spot prices. The VAR Engel Granger causality test indicated that the spot market narrowly led the futures despite a bi-directional flow of information. The results from the VECM model proved that the futures market acted as the dominant market in the long - run. Usually, researchers have leveraged sector-wise stocks to provide insights into the futures market’s function in price discovery. For the first time, HRITHIK stocks were analyzed to examine the cause-and-effect relationship for individual stocks in India’s futures and spot markets. The study considered the pre-COVID 19 and the post-COVID 19 periods and investigated the impact of the pandemic on these stocks. The research used daily closing prices of HRITHIK stocks; however, intraday data could be more conclusive and accurate in revealing the dominant market.